Exploring the influence of age and diet on gut microbiota development in children during the first 5 years: a study from Yaoundé, Cameroon - Adjele, Jorelle Jeanne B.; Devi, Priti; Kumari, Pallawi; Yadav, Aanchal; Tchuenchieu Kamgain, Alex D.; Mouafo, Hippolyte T.; Medoua, Gabriel N.; Essia, Justin J. N.; Chauhan, Nar Singh; Pandey, Rajesh (Frontiers in Microbiology, 2024)
IntroductionThe development of the human gut microbiota is shaped by factors like delivery mode, infant feeding practices, maternal diet, and environmental conditions. Diet plays a pivotal role in determining the diversity and composition of the gut microbiome, which in turn impacts immune development and overall health during this critical period. The early years, which are vital for microbial shaping, highlight a gap in understanding how the shift from milk-based diets to solid foods influences gut microbiota development in infants and young children, particularly in Yaoundé, Cameroon.MethodsThis study involved an analysis of the gut microbiota composition in 70 children aged ≤5 years through 16S rDNA gene metagenomic sequencing of fecal metagenomic DNA. The participants were grouped into four age categories: 0–6 months, 7–12 months, 13–24 months, and 25–60 months.ResultsWe observed a reduction in microbial diversity in the younger age groups, which increased progressively with age. At the taxonomic level, our analysis identified Firmicutes as the predominant phylum, with its abundance rising in older age groups, suggesting a maturation of the microbiota characterized by distinct genera associations. In the 0–6 month age group, we noted an enrichment of Lactobacilli and Bifidobacteria, which may play a crucial role in modulating and supporting immune system development during infancy. After 6 months, we found a higher prevalence of Clostridium, Bacillus, Roseburia, and Faecalibacterium, which are associated with fiber fermentation and the production of short-chain fatty acids (SCFAs).ConclusionThese findings underscore the influence of milk products and complementary diets on gut microbiota across various age groups, promoting increased diversity essential for healthy gut development. More such studies in the LMICs would augment and strengthen understanding towards functional microbiome.